The use of quizizz learning media to improve interest in answering questions - Fajar Alamsyah (12 Waiheru, 2022)
This study aims to determine the effectiveness of using Quizizz learning media to improve students' interest in answering questions on Indonesian subjects. The type of this research is quantitative research with research subjects are students of class XII Multimedia room 1, totaling 30 people at SMKN 1 Cempaga Hulu, kab. East Kotawaringin, prov. Central Kalimantan. Data were collected by researchers using two instruments, namely tests and questionnaires. The first instrument used by the researcher in collecting data was the pre-test and post-test given by the researcher to 30 students of class XII Multimedia room 1. While the second instrument was a questionnaire in the form of a google form. The data collected were analyzed using the SPSS (Statistical Package for the Social Science) application and also analyzed quantitatively. The results of data analysis using the SPSS application show that the test results mean the pre-test is 66.66 and the mean post-test is 77.44, the mean pre-test is lower than the mean post-test, and the results of data analysis show that there is an improvement in interest to students when students answer questions about Indonesian subjects. Meanwhile, from the results of the questionnaire analysis in the form of google forms, 71% of students agree that answering questions on Indonesian subjects using Quizizz learning media is a fun activity. From the results of the data analysis, it can be concluded by the researcher that Quizizz is one of the fun and effective media to improve students' interest in answering questions at SMKN 1 Cempaga Hulu, especially for students of class XII Multimedia room 1.